The global dimensions of macroprudential policy - Richard Portes; Thorsten Beck; Willem H. Buiter; Kathryn M. Dominguez; Daniel Gros; Christian Gross; Sebnem Kalemli-Ozcan; Tuomo Peltonen; Antonio Sánchez Serrano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2020)
This report elucidates the risk channels for EU economies associated with international financial integration and provides an overview of the macroprudential policy options that are available to address these risks. It builds on the main insights from the rich academic literature developed recently to create a narrative of the role of global variables for the conduct of macroprudential policy at a national level. The report reviews the evidence on the cross-border spillovers of domestic macroprudential policies (MPPs). It also highlights key policy areas for making macroprudential policy as effective as possible.
Keywords: 330; Finanzmarktaufsicht; Finanzmarkt; Internationale Konjunktur; Systemrisiko; EU-Staaten; Welt